Incidentalome in Neurogenetics: Pathogenic Variant of NSD1 in a Patient With Spinocerebellar Ataxia (SCA) - Velasco, Harvy; Ramírez-Montaño, Diana (Frontiers in Genetics, 2018)
Background: Genetic studies of late-onset sporadic ataxias (>40 years of age) are not routinely indicated. For unresolved cases, next-generation sequencing (NGS) tools, such as whole-exome sequencing (WES), are available for a definitive diagnosis. Case presentation: Our patient is a woman with a usual facial phenotype and anthropometry, who developed ataxia at 45 years of age, with no relevant family history and an initial clinical approach that ruled out common aetiologies. WES was performed when the patient was 54 years old. The results identified the heterozygous pathogenic variant c.248delA (p.N83MfsX4) in the nuclear receptor-binding SET domain protein 1 (NSD1; MIM 606681) gene (related to Sotos syndrome), which was not associated with ataxia and is not related to the patient’s phenotype. Sanger sequencing of NSD1 in two different laboratories confirmed the variant. Conclusions: NGS findings generally offer valuable information that can be used for clinical decision-making. However, an incidental finding that leads to defining new clinical and bioethical actions is also possible. Consequently, the biological importance of this type of genetic “incidentalome” must be determined.